Left-handedness and musculoskeletal discomfort in students (Journal of Accessibility and Design for All, 2022)
School furniture design is based on the right-handed population since left-handedness is uncommon. In the classroom, left-handed students are forced to use the chair that was designed for the right-handed. The awkward posture caused by the improper chair may contribute to musculoskeletal discomfort. This study aimed to evaluate the benefit of using an ambidextrous chair to accommodate left-handed students. Nordic Musculoskeletal Questionnaire was given to 14 subjects to identify their health problems related to the chair in the classroom. The NMQ showed that students often perform awkward postures and experience pain afterwards. To validate the ambidextrous chair, the subjects were asked to perform writing while sitting on both the existing and modified chairs. Then, the angles of lateral flexion of their neck and lower back from upright sitting posture were compared. Paired t-test evaluation showed that the ambidextrous chair reduced lateral flexion. Developing proper school furniture based on user-centred design can increase the comfort of the students. However, it may be costly and too specific for general use.